Bounded Rationality and Bounded Reliability: A Study of Nonfamily Managers’ Entrepreneurial Behavior in Family Firms - Kotlar, Josip; Sieger, Philipp (Entrepreneurship Theory and Practice, 2019)
We use transaction cost economics to explain the individual-level entrepreneurial behavior of family and nonfamily managers in family firms. We argue that nonfamily managers exhibit lower entrepreneurial behavior than family managers, particularly after the founder’s departure from the business. Moreover, we identify an expanded set of factors through which family firms can facilitate nonfamily managers’ entrepreneurial behavior, including monitoring, incentives, distributive justice, access to the top management, and job control perceptions. We test these hypotheses in a sample of 296 family firm managers, contributing new insights on nonfamily managers and corporate entrepreneurship in family firms.